Indexes of Church Registers 1686-1885, Volume II Prince George's County, MD - Prince George's County Historical Society; Compiled by Helen W. Brown (Prince George's County Historical Society, 1979)
In two volumes, St. Paul's Parish, Prince George's Parish
A later edition was published by Heritage Books in 2006 & 2014, in two volumes, and includes more parish records. See "Indexes of Protestant Episcopal (Anglican) Church Registers of Prince George's County, Maryland, 1686-1885, Vol 1 & 2."